2014
DOI: 10.1080/17429145.2014.890751
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid increases tolerance to oxidative stress induced by hydrogen peroxide accumulation in leaves of cadmium-exposed flax (Linum usitatissimum L.)

Abstract: 2014) Salicylic acid increases tolerance to oxidative stress induced by hydrogen peroxide accumulation in leaves of cadmium-exposed flax (Linum usitatissimum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 46 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…Correspondingly, the previous report was shown that catalase genes ( CAT1 , CAT2 , and CAT3 ) from maize differently responded to exogenous SA application [ 55 ]. This event supported the idea that SA may cause oxidative stress via an increase of H 2 O 2 level [ 59 ]; however, pretreatment of plants with the suitable concentrations of SA might induce defense-related genes in scavenging H 2 O 2 [ 36 ]. The increase of three different catalase genes expression in hot pepper and small radish can play an important role in response to environmental stresses [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 64%
“…Correspondingly, the previous report was shown that catalase genes ( CAT1 , CAT2 , and CAT3 ) from maize differently responded to exogenous SA application [ 55 ]. This event supported the idea that SA may cause oxidative stress via an increase of H 2 O 2 level [ 59 ]; however, pretreatment of plants with the suitable concentrations of SA might induce defense-related genes in scavenging H 2 O 2 [ 36 ]. The increase of three different catalase genes expression in hot pepper and small radish can play an important role in response to environmental stresses [ 60 , 61 ].…”
Section: Discussionsupporting
confidence: 64%
“…This ROS detoxification induced by SA also associated with improved photosystem II (PSII) efficiency. Belkadhi et al [147] showed that Linum usitatissimum plants showed a lower amount of lipid and protein oxidation and membrane oxidation under Cd stress when pretreated with SA. This protection was availed by the enhanced activities of SOD, GPX, and APX as well as the 2,2 0 -diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and ferricreducing antioxidant power (FRAP).…”
Section: Salicylic Acid and Ros Detoxificationmentioning
confidence: 99%
“…They also concluded that NO may act as downstream of SA signaling in the reduction of induced oxidative damage [152]. SA-mediated H 2 O 2 signaling and subsequent Cd stress tolerance was revealed in L. usitatissimum [147]. Seedlings pretreated with 250 or 1000 μM SA resulted in enhanced production of H 2 O 2 because of inhibited CAT activity.…”
Section: Interaction Of Sa With Other Signaling Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, they also play a signaling role, and changes in production of ROS can act as a signal that changes the transcription of genes, thereby favoring the adaptation of plants to stresses (Jajic et al 2015). Among ROS species, the hydrogen peroxide (H2O2) is an important compound involved in plant response to different environmental stressors (Belkadhi et al 2014, Jajic et al 2015. Moreover, H2O2 protects photosynthetic membranes during light stress (Laloi et al 2007).…”
Section: Introductionmentioning
confidence: 99%